Designer mobile residential module as an element of infrastructure development in the sphere of the southern region of Ukraine - Zhiltsova, G.; Gordilev, N. (Theory and practice of design, 2017)
The article deals with the issues of actual design trends and the application of innovative technologies in the creation of mobile housing units in order to develop the tourism industry of the Southern region of Ukraine. The task was to identify the target audience, a variety of recreational opportunities of the territory, and advantages of construction mobile homes in the process of further development of the region. In the empirical part of the study the main concern was finding out the factors, which affect on forming of successful mobile building projects. Among them: simple process of moving and assembling mobile construction; providing comfort needs of modern people; minimizing the impact of human activity on the environment; a combination of innovative technology and current design trends; compliance with external characteristics of the housing unit and the natural landscape.